1995
DOI: 10.1016/0885-3924(95)00052-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter assessment of the Edmonton staging system for cancer pain

Abstract: Two hundred and seventy-seven patients were admitted to this prospective multicenter study in order to assess the accuracy of a staging system for cancer pain. The staging system (SS) was completed by a trained physician during the initial consultation. This system included the assessment of pain mechanism (PM, neuropathic versus nonneuropathic), pain characteristic (PC, continuous versus incidental), previous opioid dose (OD), cognitive function (CF), psychological distress (PD), tolerance (T), past history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
1
11

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(165 citation statements)
references
References 15 publications
2
151
1
11
Order By: Relevance
“…Indeed, we found that 150/284 (53%) of all diagnosed pain syndromes were complicated by poor prognostic factors, such as neuropathic and incidental pain features, associated with poor pain control by opioids [20]. Moreover the pain intensity was rated as 5 or above (moderate to severe pain) in 69%, and those values are considered substantial and interfering with the quality of life [11].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that 150/284 (53%) of all diagnosed pain syndromes were complicated by poor prognostic factors, such as neuropathic and incidental pain features, associated with poor pain control by opioids [20]. Moreover the pain intensity was rated as 5 or above (moderate to severe pain) in 69%, and those values are considered substantial and interfering with the quality of life [11].…”
Section: Discussionmentioning
confidence: 99%
“…The 'opioid escalation index' (OEI) is a dynamic tool useful to describe a trend in opioid response, where multiple factors can be identified. On the other hand such a factor, expressed in the previous version of ESS as 'tolerance', 16 had been already removed from the staging system. As expected, in this study OEI was associated with a response 'b', that is good pain control requiring more aggressive opioid escalation, exactly reproducing the meaning of this tool, that is the therapeutic effort to achieve a meaningful outcome.…”
Section: Mild Pain N = 28mentioning
confidence: 99%
“…Furthermore, a multidimensional assessment is essential, particularly with a view to identifying any underlying poor prognostic factors for pain control, such as a neuropathic pain component, incidental pain, opioid tolerance, somatization of psychologic distress, or a history of chemical coping through drug or alcohol abuse. 125 Identification of some of these factors at an early stage could direct the physician to use more effective pharmacologic and nonpharmacologic intervention and therefore help prevent the occurrence of cognitive dysfunction associated with escalating opioid doses. Strategies for prevention of initial or recurrent episodes are summarized in Table 6.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…• Educate family regarding recognition of potential neurotoxic features such as myoclonus 106 • Objectively monitor cognition 108,111 • Adjust dose in elderly patients 96,97 • Discontinue or minimize use of all unnecessary medications, especially other psychotropics 4 • Adjust dose for impaired renal function [93][94][95] • Maintain adequate hydration and use diuretics cautiously 4 • Perform a multidimensional assessment 127,128 • Identify poor prognosticators for pain control: neuropathic and incidental pain, somatization, tolerance, and addiction history 125 • Optimal utilization of other therapies e.g., appropriate use of adjuvant and other therapies, maximize nonpharmacologic interventions 67 • Adopt a proactive approach: early intervention with management strategies to possibly avert a full-blown delirium syndrome 17 patient group noted a decrease of approximately 60% in the chart recordings of agitated impaired mental status in association with a practice change of increased opioid rotation, hydration, and objective cognitive monitoring. 133 An open prospective study of hospice patients by Maddocks et al found a significant improvement in mental state in patients with morphine-associated delirium, who were switched to oxycodone.…”
Section: Table 6 Proposed Strategies To Prevent Opioid-induced Cognitmentioning
confidence: 99%